Phenolic Compounds with In Vitro Activity against Respiratory Syncytial Virus from the Nigerian Lichen Ramalina farinacea - Lai, Daowan; Odimegwu, Damian C.; Esimone, Charles; Grunwald, Thomas; Proksch, Peter (Planta Medica, 2013)
The extract of the Nigerian lichen Ramalina farinacea showed inhibitory activity against the respiratory syncytial virus in a preliminary assay. A follow-up chemical investigation of this lichen led to the isolation of thirteen phenolic compounds (1–13), including one new hydroquinone depside, designated 5-hydroxysekikaic acid (1), and one new orsellinic acid derivative, 2,3-dihydroxy-4-methoxy-6-pentylbenzoic acid (8). Their structures were unambiguously determined by analysis of 1D and 2D NMR and mass spectroscopic data, as well as by comparison with literature data. Compound 1 was found to partially convert to a 1,4-benzoquinone derivative (1a) during storage. The antiviral activities of the isolated compounds were evaluated against the respiratory syncytial virus. Among them, sekikaic acid (2) showed potent inhibition towards a recombinant strain rg respiratory syncytial virus (IC50 5.69 µg/mL) and respiratory syncytial virus A2 strain (IC50 7.73 µg/mL). The effect of sekikaic acid on the cell viability of HEp2 and Vero cell lines was investigated, and the time of addition assay revealed that sekikaic acid clearly interferes with viral replication at a viral post-entry step, which is over 1.3-fold more active than the control ribavirin at 4 hours postinfection addition. Furthermore, sekikaic acid did not display virucidal activity at concentrations below the TC50, whereas the parental extract did.
Keywords: Ramalinaceae; Ramalina farinacea; structure elucidation; sekikaic acid; antiviral; respiratory syncytial virus